Animated version of figure 8 from Stress and deformation characteristics of sea ice in a high-resolution, anisotropic sea ice model - H. D. B. S. Heorton; D. L. Feltham; M. Tsamados (2018)
Animation of 72 hours of winds with a confinemnt ratio of -0.4. The winds rotated about the centre of the grid by 45 degrees every 12 hours.